Leverage and capital structure determinants of Chinese listed companies. - Ferrarini, Benno (Economics working papers., 2017)
In this paper, quantile regressions are applied to a rich dataset of Chinese listed companies contained in Standard & Poor IQ Capital database. Authors find higher sensitivity over time of corporate leverage to some of its key determinants, particularly for firms at the upper margin of the distribution. In particular, profitability increasingly acts as a curb on corporate leverage. At a time of falling profitability across the Chinese nonfinancial corporate sector, this eases the brake on leverage and may contribute to its continuing increase.